Ilokano Dictionary - Constantino, Ernesto (University of Hawai'i Press, 2018)
Ilokano is a member of the Philippine group of Austronesian languages. It ranks third among the major languages of the Philippines, being spoken by just over 12 percent of the population. Widely spoken throughout the Philippines, Ilokano is the dominant language of most of the provinces of Northern Luzon and is used as a lingua franca by non-Ilokano speakers in this area. Settlers have also carried the language to Mindoro and to several areas in Mindanao.This dictionary contains some 7,000 Ilokano entries. Many of the entries are illustrated by Ilokano sentences to clarify usage.